Writing religion: the making of Turkish Alevi Islam - Dreßler, Markus (Reflection and theory in the study of religion series, 2013)
Markus Dressler tells the story of how a number of marginalized socioreligious communities, traditionally and derogatorily referred to as Kizilbas ('Redhead'), captured the attention of the late Ottoman and early Republican Turkish nationalists and were gradually integrated into the newly formulated identity of secular Turkish nationalists